2017
DOI: 10.1182/blood-2017-01-757328
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the prothrombotic role of NETs

Abstract: Conflict-of-interest disclosure: M.S.R. has received research funding and consultancy fees from Celgene, Novartis, Amgen, Morphosys, Takeda, and Janssen. n REFERENCES Demystifying the prothrombotic role of NETs Christian Schulz and Steffen Massberg KLINIKUM DER LUDWIG-MAXIMILIANS-UNIVERSITÄT MÜNCHENIn this issue of Blood, Noubouossie and colleagues report surprising findings on the role of neutrophil-derived nuclear material in blood coagulation. The authors provide evidence that, in contrast to DNA and histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
(10 reference statements)
2
10
0
Order By: Relevance
“…In addition to H3Cit levels, we also determined the levels of cfDNA and nucleosomes, which are essential components of NETs [2]. In recent studies, it was shown that such NET breakdown products rather than intact NETs induce coagulation [38,39]. However, elevated levels as such do not necessarily indicate increased NET formation, as apoptotic and necrotic cell death are other potential sources of cfDNA and nucleosome release [40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to H3Cit levels, we also determined the levels of cfDNA and nucleosomes, which are essential components of NETs [2]. In recent studies, it was shown that such NET breakdown products rather than intact NETs induce coagulation [38,39]. However, elevated levels as such do not necessarily indicate increased NET formation, as apoptotic and necrotic cell death are other potential sources of cfDNA and nucleosome release [40].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has been observed that NETs can trigger platelet activation and that activated platelets can, in turn, promote NETosis [89,90]. Furthermore, it seems that intact NETs may not be required, but rather that isolated NETs components such as cell-free DNA, histones or liberated serine proteases may provide the crucial impetus [90,91]. Furthermore, it seems that intact NETs may not be required, but rather that isolated NETs components such as cell-free DNA, histones or liberated serine proteases may provide the crucial impetus [90,91].…”
Section: Pregnancy Nets and Thrombosismentioning
confidence: 99%
“…The mechanism whereby NETs promote coagulation is currently unclear, but may involve interaction with platelets [89]. In this context, it has been observed that NETs can trigger platelet activation and that activated platelets can, in turn, promote NETosis [89,90]. If left unchecked, this could provide the basis for autocatalytic loop with potentially disastrous consequences.…”
Section: Pregnancy Nets and Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the procoagulant activity of NETs. cfDNA triggers thrombin generation via activation of the contact pathway and elevated levels of circulating cfDNA is a hallmark feature in patients with deep vein thrombosis and sepsis ( 4 7 ).…”
Section: Introductionmentioning
confidence: 99%